CITY WELL-BEING SPATIAL DIFFERENTIATION AS THE URBOGEOSYSTEM FUNCTION ASSESSMENT WITH GIS-TOOLS (CASE STUDY OF KHARKIV) - Чуєв, Олексій; Костріков, Сергій (Human Geography Journal, 2015)
This paper recognizes the original research approach due to the urbogeosystem investigation through the GIS-tools with a megalopolis case study. Specifically the city population well-being spatial differentiation methods have been described, and this parameter is considered as the urbogeosystem function upon this description. The analysis of city population supply of city social / human infrastructural facilities has been provided. The infrastructural facilities have been classified according to their impact on city population well-being. Consequently Kharkiv city area has been regionalized by the population well-being level. Reasonability of GIS-tool involvement into urbogeosystem research has been proved.